The Forgotten Graffiti of the Templum Pacis in Rome - Tucci, Pier Luigi (Archäologischer Anzeiger, 2024)
The graffiti found in 1825 and 1999 in the square of the Temple of Peace, a monumental architectural complex built by Vespasian in A.D. 71–75 near the Forums of Caesar and Augustus, have been completely overlooked to date. In particular, the reports and publications on the post-1999 excavations have never mentioned the existence of the scratched image of a charioteer, despite the growing interest in graffiti and charioteers in the Roman world. The first part of the present article reviews the complete documentation of the digs made in 1825; then, it examines the graffiti that came to light in 1999, with a focus on the figure of the charioteer that, with its height of nearly 1 m, is the largest identified in Rome to date. The author supports the identification of the figure through comparisons with images of charioteers from various media and examines how it was carved (a drawing of the graffiti is presented here for the very first time) along with its state of preservation – the figure is fading away because since 1999 it has been exposed to the elements on the top surface of a marble step. The final section discusses why and when that image was scratched in the Temple of Peace, thus providing a glimpse into everyday life in late-antique Rome, and how it has survived until today.